Diprosopus Tetrophthalmus Including Radiological and Post-Partum Images- A Case Report - Sah, Dambar; Jha, Akhilesh Kumar; Jha, Rakesh Kumar; Sah, Madhu (Med Phoenix, 2023)
Introduction: Conjoint twinning is very uncommon with an incidence of approximately 1:50,000 to 1:100,000. Diprosopus tetrophthalmus is the rarest variant of conjoined twinning which results from incomplete monozygotic, monochorionic and monoamniotic twin division associated with multiple congenital malformations.  A 25 years old female patient at 26 weeks of gestation having single gravida (primi) and no significant family history was referred to our radiology department for anomalies scan. Transabdominal obstetric ultrasound showed the fetus with one head, two faces, two legs, two hands, one thorax, one abdomen and a single spinal cord with deformed spine. The aim of this case report was to present and discuss a case of Diprosopus tetrophthalmus (craniofacial duplication) a rare variant of conjoined twins resulted from incomplete monozygotic, monochorionic and monoamniotic twin division which help in prenatal counseling to the patient and its management.